Analytical Characterization of a Solution Cathode Glow Discharge with an Interference Filter Wheel for Spectral Discrimination. (22nd September 2018) - Zheng, Peichao; Zhai, Xiang; Wang, Jinmei; Tang, Pengfei
ABSTRACT: Solution cathode glow discharge–atomic emission spectrometry (SCGD–AES) has attracted increasing attention in recent years in water and environmental analysis. In this article, the traditional spectrometer was replaced by an interference filter wheel for spectral discrimination using SCGD–AES. The aforementioned interference filters selected the spectral lines of Na, K, Ca, Li, Sr, Rb, and Cs. These spectral signals were transferred to weak currents using a photomultiplier tube and amplified by a picoammeter. The solution flow rate, discharge current and slit width were optimized individually. The analytical performance of SCGD coupled with an interference filter wheel was studied for atomic emission (SCGD–IFW–AES). The results show that the limits of detection for Na, K, Ca, Li, Sr, Rb, and Cs were 0.16, 0.36, 107, 0.53, 330, 1.93, and 13.58 µg/L, respectively. The relative standard deviations of the spectral intensities for the seven elements were 0.58, 0.94, 0.69, 0.70, 0.63, 0.67, and 0.65%, which indicated that the system operated stably. Matrix effect experiments were performed to study the effect of different concentrations of Na on the spectral intensities of K and Ca. Based on these measurements, the concentration of K in physiological saline was determined to be 0.534 mg/L by SCGD–IFW–AES.